Modern technologies and the management of sports and leisure buyer engagement - Widawska-Stanisz, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The market for sports and leisure services is constantly evolving. Polish consumers are more often interested in the offer of sports and leisure enterprises such as fitness clubs, water parks, gyms, or sports and leisure centres, recognising the importance of looking after their health and physical fitness. After a period of isolation during the COVID-19 pandemic, physical activity is even more frequently regarded as fundamental to maintaining health and fitness, harmony and balance in life. Currently, all fitness-related activities are classified as leisure time mega trends (e.g. work-life balance). Modern technologies are another noticeable trend, which is beginning to accompany people in physical activity as well. They help streamline the service delivery process and apply a personalised approach to the customer. We are not just talking about today’s most popular social media, apps and activity monitoring devices. QR codes, geolocation, gamification, sports coaching, and others can be applied in business practice. The objective of the article was to show the specifics of the sports and leisure industry, characterise the dominant technological solutions and identify the opportunities they can provide for sports and leisure businesses. It was assumed that modern technologies could be complementary and successfully used both to promote physical activity itself and to build the commitment of buyers of services provided by such companies. The research used qualitative and quantitative methods, as well as literature analysis. As the analysis of the survey results and observation of the market has shown, modern technologies motivate participants of physical activity, while sports and leisure companies are beginning to recognise their advantages in promoting their services. The article emphasises the complementarity of solutions and their comprehensiveness, as well as possible implications in the service activity of sports and leisure enterprises. The result of the analysis is a proposal for a set of useful features and solutions dedicated to companies providing sports and leisure services. By applying the proposed solutions, these companies can become more innovative, while their customers will be more satisfied.
Keywords: marketing; promotion; sports and leisure services; modern technology; buyer